AB0379 GENDER DIFFERENCES IN RHEUMATOID ARTHRITIS: EFFECT OF ANTI-TUMOR NECROSIS FACTOR THERAPY. (June 2019) - Gioia, Chiara; Spinelli, Francesca; Priori, Roberta; Iannuccelli, Cristina; Lucchino, Bruno; Vestri, Annarita; Valesini, Guido; Franco, Manuela DI
Abstract : Background: Rheumatoid arthritis (RA) is more prevalent in women than men (F:M=4:1), due to hormonal, genetic and environment factors. Women present higher disease activity markers as Disease Activity Score-28 (DAS28) and Health Assessment Questionnaire (HAQ), at the onset and after c-DMARDs therapy, without correlation with radiographic damage. Objectives: The purpose of this study was to assess gender differences in RA patients after anti- tumor necrosis factor (TNF) α treatment. Methods: Ninety-six patients were enrolled at the beginning of anti-TNF α therapy (etanercept and adalimumab). All patients satisfied 1987 and 2010 ACR criteria for RA. They underwent to clinical and clinimetric evaluation at baseline (T0) and after three (T3) and six (T6) months of therapy with: tender and swollen joints, Visual Analogic Scale (VAS) pain, VAS patient and physician, DAS28, Clinical/Simplified clinical disease activity index (CDAI/SDAI) and HAQ. The evaluation of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), Rheumatoid Factor (RF) and anti-citrullinated protein antibody (ACPA) was performed in all patients. Results: Among these patients, 70 were women and 26 men; 81 patients (58 female, 23 male) started etanercept and 15 adalimumab (12 female, 3 male). They presented a mean age of 56.4 ± 14.5 years (women 55.2 ± 15.4, men 60 ± 11.2) and mean disease duration of 11 ± 6.8 years (woman 11.51 ± 6.3, men 9.6 ± 8.1). Both women and men had a DAS28 reduction after 3 and 6 months therapy (p<0.05) but DAS28 in women was higher than men at T0, T3 and T6 (p<0.05). Women presented higher number of tender joints in all evaluations, and more swollen joints than men at T0 and T6 (p<0.05). Women felt more active disease at T6 (VAS patient) (p<0.05). CDAI was higher in woman after 3 and 6 months (p<0.05). There were no differences about physician evaluation, inflammation markers, RF and ACPA titles. Conclusion: In this study, both women and men had a good response to anti-TNF treatment but women presented worse clinical response. Female gender resulted the only variable associated with DAS28 reduction differences. We could hypothesize that beyond to biological factors, also social contest, daily life and work activity could explain a worse impact of disease on women. References: [1] Neovius M, Ann Rheum Dis 2011; [2] O.L. Quintero, et al., Journal of Autoimmunity 2012. [3] M Ahlm áen, Ann Rheum Dis 2010. [4] Jawaheer, et al, The Journal of Rheumatology 2010. [5] Jawaheer, et al, The Journal of Rheumatology 2012. [6] Arnett FC, Arthritis Rheum 1988. [7] Aletaha D, Arthritis Rheum 2010. Disclosure of Interests: None declared